Pengelompokan Provinsi Berdasarkan Indikator Ekonomi, Pendidikan, Kesehatan, dan Kriminalitas di Indonesia Menggunakan Algoritma Centroid Linkage - Candra, Yossy; Goejantoro, Rito; Dani, Andrea Tri Rian (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2024)
With its rich cultural diversity and abundant natural resource potential, Indonesia still faces various social science problems. Economic inequality, low quality of education, limited access to health, and high crime rates are social problems that hit various provinces in Indonesia. This research was conducted to group provinces in Indonesia based on social indicators, which include economy, education, health, and crime. This research uses cluster analysis with the Centroid Linkage algorithm to group provinces in Indonesia. The Centroid Linkage algorithm was chosen because of its advantages in producing optimal grouping. Test cluster validity using the Silhouette Coefficient (SC). The case studies used are variables that are thought to be related to economic, health, education, and crime problems in 34 provinces in Indonesia in 2021. Based on the analysis, the grouping results using the Centroid Linkage algorithm show that the optimal number of clusters is 2, with an SC value of 0.538. Cluster 1 consists of 33 provinces, and Cluster 2 consists of only one province, DKI Jakarta.